Reducción de ruido impulsivo en secuencias de video en color de resonancia magnética - Florentín Nuñez, María Nieves (2009)
This article presents a new technique for the decrease of impulsive noise for the switching median filters. The filter was based on the similarity that may exist among successive images in order to preserve more details of the sequences of video and to efficiently reduce impulsive noise. We have considered several test videos to determine the efficiency of the new proposed filter. The results of the simulation showed that the proposed method provides better performance than other filter.